Public Infrastructures, Public Consumption, and Welfare in a New-Open-Economy-Macro Model - Ganelli, Giovanni (IMF Working Papers; Working Paper ;, 2007)
This paper focuses on the trade-off faced by governments in deciding the allocation of public expenditures between productivity-enhancing public infrastructures and utility-enhancing public consumption. From the modeling point of view, the paper augments a standard New Open Economy Macroeconomics (NOEM) model by introducing productive public infrastructures. The results show that a temporary increase in the domestic stock of public capital financed by a reduction in public consumption reduces domestic welfare in the short run because the temporary gains from higher productivity do not compensate domestic residents for the utility loss due to lower public consumption. If the policy shift is permanent domestic utility is likely to increase, while foreign residents suffer short-run welfare losses but benefit from welfare gains in the long run. This analysis implies that a permanent domestic reallocation of public spending might result in a virtuous global technological cycle.